Optical navigation system and optical navigation apparatus thereof - CHUNG, CHING-LIN; CHANG, YEN-MIN (2014)
An optical navigation system and an optical navigation apparatus thereof are provided. The optical navigation system comprises a host and the optical navigation apparatus. The host detects a running program to generate a control signal. The optical navigation apparatus, which is connected to the host via a wireless way, receives the control signal to perform a performance configuration according to the control signal for adjusting an image data amount required to be processed.